Hypercalcemia Associated with Extramammary Paget’s Disease - Sato, Tetsuko; Wada, Yoshihisa; Kamitani, Nobuhiko; Yamamoto, Takenobu; Aoyama, Yumi; Fujimoto, Wataru; Tanaka, Ryo (Case reports in oncology, 2020)
Hypercalcemia of malignancy occurs in up to one third of patients at some point during the course of their advanced stage. The majority of them is caused by humoral hypercalcemia of malignancy due to systemic secretion of parathyroid hormone–related protein (PTHrP) by tumor cells. Extramammary Paget’s disease is a slow-growing cutaneous malignancy commonly limited to the epidermis of the anogenital region, but rarely becomes invasive and metastatic to distant sites. Herein, we report a 70-year-old male patient with metastatic extramammary Paget’s disease. He consulted our hospital with altered consciousness and tumor in his genital area. Physical examination revealed erythematous plaque with a tumor on the scrotum and perineum. It was diagnosed as extramammary Paget’s disease (multiple liver metastases and multiple lymph node metastases by skin biopsy and image examination). Increases in serum-corrected calcium and PTHrP-intact levels (15.3 mg/dL and 66.1 pg/L, respectively) were confirmed. PTHrP immunohistochemistry showed positive staining in the tumor cells. We diagnosed humoral hypercalcemia of malignancy. We treated hypercalcemia with saline, furosemide, zoledronic acid, and elcatonin. Regarding the local control of the tumor, 30 Gy/10 Fr electron beam therapy was performed. However, treatment with zoledronic acid was only temporally effective to correct hypercalcemia, and an increased serum calcium level developed again. Concurrently, the liver metastases were rapidly enlarged, and his general condition gradually deteriorated. The patient died on day 55. When patients with extramammary Paget’s disease show unconsciousness, serum calcium level should be measured and PTHrP-producing tumor distinguished.